Magnesium ions mitigate biofilm formation of Bacillus species via downregulation of matrix genes expression - Oknin, Hilla; Steinberg, Doron; Shemesh, Moshe (Frontiers in Microbiology, 2015)
The objective of this study was to investigate the effect of Mg2+ ions on biofilm formation by Bacillus species, which are considered as problematic microorganisms in the food industry. We found that magnesium ions are capable to inhibit significantly biofilm formation of Bacillus species at 50 mM concentration and higher. We further report that Mg2+ ions don't inhibit bacterial growth at elevated concentrations; hence, the mode of action of Mg2+ ions is apparently specific to inhibition of biofilm formation. Biofilm formation depends on the synthesis of extracellular matrix, whose production in Bacillus subtilis is specified by two major operons: the epsA-O and tapA operons. We analyzed the effect of Mg2+ ions on matrix gene expression using transcriptional fusions of the promoters for eps and tapA to the gene encoding β galactosidase. The expression of the two matrix operons was reduced drastically in response to Mg2+ ions suggesting about their inhibitory effect on expression of the matrix genes in B. subtilis. Since the matrix gene expression is tightly controlled by Spo0A dependent pathway, we conclude that Mg2+ ions could affect the signal transduction for biofilm formation through this pathway.